Effects of inoculation with lignocellulose-degrading microorganisms on antibiotic resistance genes and the bacterial community during co-composting of swine manure with spent mushroom substrate. (September 2019) - Hu, Ting; Wang, Xiaojuan; Zhen, Lisha; Gu, Jie; Zhang, Kaiyu; Wang, Qianzhi; Ma, Jiyue; Peng, Huiling
Abstract: Composting is usually employed to treat livestock manure, and inoculation with lignocellulose-degrading microorganisms can enhance the quality of compost. In this study, lignocellulose-degrading microorganisms were inoculated at two levels (uninoculated control = 0%, and T treatment = 10%) during co-composting of swine manure with spent mushroom substrate, and their effects on antibiotic resistance genes (ARGs) and the bacterial community were investigated. Inoculation with lignocellulose-degrading microorganisms caused greater decreases in 6/11 ARGs and 3/4 mobile genetic elements than the control. The total relative abundances of ARGs increased by 0.23 logs in the control but decreased by 0.08 logs in the T treatment after co-composting. The bacterial community was clustered according to the composting time in the two treatments, where inoculation mainly affected the bacterial community during the mesophilic phase. Redundancy analysis and network analysis showed that the bacterial community succession had important effects on the variations in ARGs. Inoculation with lignocellulose-degrading microorganisms led to the reduction of ARGs, which was significantly correlated with the abundances of potential host bacteria for ARGs. Thus, inoculation with lignocellulose-degrading microorganisms could decrease the risk of ARGs spreading and make compost products more security. Graphical abstract: Image 1 Highlights: Inoculation with microorganisms led to greater decreases in 6/11 ARGs and 3/4 MGEs. Inoculation with microorganisms affected bacterial community in mesophilic phase. Bacterial community structure had important effects on the variations in ARGs. Inoculation with microorganisms could decrease the risk of ARGs in compost product. Abstract : Inoculation with lignocellulose-degrading microorganisms during co-composting could reduce ARGs, inhibit pathogens, and make compost products safer.